Awig-Awig Effectiveness In Protection Of Marine Natural Resources, Indigenous Communities Of Lombok - Wiwin Yulianingsih; Frans Simangunsong; Maria Novita Apriyani (International Journal of Educational Research & Social Sciences, 2021)
Sources of income for fishermen are not only generated through fishery resources but also carry out fish cultivation in ponds, seaweed cultivation and traditional fish processing. Fish farming, and development activities are carried out by fishermen because the results obtained from the sea are not sufficient for their daily needs. This study is to determine the effectiveness of the application of Awig-Awig in the protection of marine natural resources of the indigenous peoples of East Lombok. The approach chosen in this research is empirical juridical. The choice of this approach was taken because what will be studied in addition to laws and regulations is also the influence of customary law that develops in society, especially in East Lombok. Awig-awig Teluk Jor area is divided into 13 chapters and consists of 17 articles. The chapters contained in the awig-awig of the Teluk Jor area regulates general provisions, types and facilities of fishing gear, fishing areas, and the operation of fishing gear, cultivation, conservation, pollution of the coastal environment, security, shipping, institutions and sources. management funds, sanctions, procedures for administering sanctions, additional and transitional rule, and closings. About  conservation, the awig-awig of the Teluk Jor area regulate  the use of mangroves that can be used for research, tourism, and other business activities that do not damage the surrounding environment as well as protection from illegal logging, and conversion of mangrove land into ponds.